Aggregation-based spectrum assignment in cognitive radio networks - Rostami, Soheil; Arshad, Kamran; Rapajic, Predrag (2013 International Conference on Advanced Computing and Communication Systems, 2013)
Cognitive radio has been introduced as a promising solution to the apparent problem of spectrum scarcity by exploiting unused portions of spectrum. The available spectrum bands or whitespaces are usually fragmented and discontinuous. In order to fulfil ever increasing demand for higher bandwidth, cognitive radio can exploit multiple whitespaces together to satisfy users' requirements by aggregating contiguous or fragmented portions of spectrum. In this paper, a novel genetic algorithm based spectrum aggregation scheme is proposed by taking into consideration the realistic constraints of co-channel interference and maximum aggregation span. Numerical results show that our method significantly increases the spectrum utilisation compared with the state-of-the-art solutions.